2017
DOI: 10.1111/ijn.12604
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Parental Feeding Behaviours Questionnaire for Indonesian parents of young children

Abstract: The PFBQ is a valid and reliable instrument; however, more studies are required to identify acceptable tools to measure more culturally diverse range of parental feeding behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The questionnaire in this study is based on the questionnaire of Lusmilasari ( 47 ), and was truncated and modified according to the feeding characteristics of infants in China. The general principle is that higher scores indicate better feeding behavior, the results showed that mothers’ feeding behavior was at a high level.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire in this study is based on the questionnaire of Lusmilasari ( 47 ), and was truncated and modified according to the feeding characteristics of infants in China. The general principle is that higher scores indicate better feeding behavior, the results showed that mothers’ feeding behavior was at a high level.…”
Section: Discussionmentioning
confidence: 99%